Subacute Thyroiditis Associated with COVID-19 - Eugenia Campos-Barrera; Teresa Alvarez-Cisneros; Mario Davalos-Fuentes (Case Reports in Endocrinology)
Subacute thyroiditis is a self-limiting inflammatory disorder, characterized by neck pain or discomfort, a tender diffuse goiter, and sometimes a transient episode of hyperthyroidism followed by euthyroidism and sometimes hypothyroidism. There is usually a normalization of thyroid function within a few weeks. Subacute thyroiditis has a higher incidence in summer and has been linked to a viral or bacterial upper respiratory postinfection inflammatory response. We hereby describe the case of a previously healthy 37-year-old female presenting with subacute thyroiditis associated with a very mild presentation of COVID-19. As most patients with SARS-Cov-2 are asymptomatic, we suggest to rule out SARS-Cov-2 infection in patients presenting with symptoms suggesting SAT.